Green synthesis of 6-cyano-2,2-dimethyl-2-H-1-benzopyran and its subsequent enantioselective epoxidation - Romanelli, Gustavo Pablo (2015)
Abstract The clean synthesis of 6-cyano-2,2-dimethyl-2- H -1-benzopyran epoxide starting from 3-methyl-2-butenal is reported using recyclable catalysts. H₄PMo₁₁VO₄₀ (PMo₁₁V) and (PyH)₃HPMo₁₁VO₄₀ (Py₃ –PMo₁₁V) Keggin-type heteropolyacids were used to synthesize 6-cyano-2,2-dimethyl-2- H -1-benzopyran in two steps with 35% yield. This is an alternative procedure to the traditional methodology with pyridine or picoline as catalyst, where 6-cyano-2,2-dimethyl-2- H -1-benzopyran is obtained by condensation of 4-cyanophenol with 1,1-diethoxy-3-methyl-2-butene. The 6-cyano-2,2-dimethyl-2- H -1-benzopyran epoxide was obtained using Jacobsen-type catalysts, and in situ generated dimethyldioxirane (DMD) as oxidizing agent, that in comparison to m -CPBA/4-NMO and NaOCl/4-PPNO did not degrade the catalyst. In presence of 4-phenylpyridine N -oxide (4-PPNO) at 4 °C, enantioselectivities of 87% for 3S,4S-epoxide and 68% for 3R,4R-epoxide were obtained with the S,S- and R,R-Jacobsen catalysts, respectively. Overall yield was approximately 17% for 3S,4S-epoxide.